The Perceptions of Teachers at the Secondary Schools in Bani Obaid District at Irbid City for their Schools by Considering the Schools as Learning Organizations - Al-Essa, Asem Abdullah (Journal of Educational and Psychological Sciences, 2020)
This study investigates the perceptions of teachers at the secondary schools in Bani Obaid district at Irbid city for their schools by considering the schools as learning organizations. This study discovers the differences in participant responses that are related to their perceptions by considering the schools as educated organizations based on the following factors: gender, qualifications, and years of experience. To achieve the objectives of the study, the researcher follows the descriptive methodology by preparing a questionnaire which includes (35) parts. The sample of the study consists of (250) male and female teachers in the secondary schools at Bani Obaid district. They were collected randomly from the total number of teachers in that district which is (413). They represent (60%) of the teachers in the district. The perceptions of the teachers of the secondary schools at Bani Obaid district at Irbid city for their schools as educated organizations got (5,64) for the highest average based on the general performance using the tool. The results based on the scopes of the study are as the following: working as a team got the highest average (3.91). The followed scope is the mental models (3.66). The third one is related to the personal ability with average (3.91) then the collective vision with average (3.50) and lastly, the critical thinking with average (3.49). There were not much significant statistical differences in level (α≤0.05) in the sample responses which are related to the study scopes and tool based on the sex and years of experience in addition to (collective vision and personal ability) dimensions based on the qualification. There were significant statistical differences in level (α≤0.05) in the sample responses which are related to the scopes of (collective vision, mental models and teamwork) based on the qualification dimension specially the bachelor degree. Based on the results of the research, the researcher recommends providing financial and moral incentives for the distinguished secondary schools to apply the principles of the educated schools.
Keywords: Educated organization; secondary schools; perceptions of teacher; Bani Obaid District